Hubungan antara Kepercayaan Diri dengan Kecemasan Bertanding pada Atlet Voli - Wijaya, Yuniko Andre; Purnomo, Jusuf Tjahjo (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Competitive anxiety is an unpleasant emotional reaction brought on by worry or fear that occurs when fear is triggered during competition. The athlete's self-confidence is one of the aspects that affects nervousness when competing. The purpose of this study is to ascertain the association between volleyball athletes levels of self-confidence and competition anxiety in Salatiga city. Quantitative research methods with a correlational design are employed. Purposive sampling was used in this study, which included a total of 90 participants. The Sport Anxiety Scale-2 (SAS) (α = 0.900) and the Self-confidence Scale (α= 0.967) were the instruments employed in this study. The analysis of the data revealed a significant inverse association between competition anxiety and selfconfidence in volleyball athletes in Salatiga city, with rs = -0.498 and α = 0.000 (< 0.01).Athletes will have low competition anxiety if they have high self-confidence, so that when athletes are able to have confidence in their abilities, it will minimize anxiety in competing.